Influence of high–low hybrid towers on the wind flow and energy of complex terrain. (November 2022) - Peng, Huaiwu; Liu, Wei; Zhang, Rikui; Li, Huaxiang; Wang, Hao; Chen, Kang
Abstract: In this paper, an Actuator Disk Model (ADM) was introduced into a commercial computational fluid dynamic software and used to simulate the wake effect of wind turbines in a wind field with complex terrain. Then, the influence of towers with difference height on wake flow and power generation can be studied, which is particularly important for the wind field design in complex terrain. The numerical results are verified by means of comparison with the measured data of Supervisory Control and Data Acquisition (SCADA). More detailed numerical results show that the optimization of the design of high and low hybrid towers with difference size wind turbines can not only make full use of the advantages of high wind speed at high altitudes, but also reasonably improve the wake flow generated by the front wind turbine and increase the power generation of the wind field. It is found that the power increment generated by the high–low hybrid towers arrangement is roughly inversely proportional to U 0 0 . 877, when only evaluating the effect of tower height; moreover, if the rotor diameter is further increased, the power gain of the hybrid arrangement scheme is roughly inversely proportional to U 0 1 . 167 . The research provides a robust and practical numerical method for the design of wind field layout and the optimization of high and low hybrid towers.